Hubungan antara Gaya Hidup Hedonis dengan Harga Diri pada Mahasiswa Generasi Z Universitas Swasta Jakarta - Putri, Adinda Ranita; Aulia, Farah (Lembaga Yasin AlSys, 2024)
University students are in a phase of self-discovery, during which a hedonistic lifestyle can influence their self-perception. This study aims to analyze the relationship between a hedonistic lifestyle and self-esteem among Generation Z students at a private university in Jakarta. The research employs a quantitative method with a correlational approach, where data were collected through questionnaires distributed to 270 students using purposive sampling techniques. The hedonistic lifestyle was measured using the Hedonistic Lifestyle Scale (Engel et al., 1994), while self-esteem was measured using the Self-Esteem Scale (Rosenberg, 1965). The results indicate a significant positive relationship between a hedonistic lifestyle and self-esteem, with a correlation coefficient of r = 0.683 and a significance level of p < 0.05. These findings suggest that students with a hedonistic lifestyle tend to have higher self-esteem. Overall, the study shows that the majority of Generation Z students at the private university in Jakarta exhibit both high self-esteem and a high hedonistic lifestyle.